2011
DOI: 10.1039/c0cp01590c
|View full text |Cite
|
Sign up to set email alerts
|

The mixed network former effect in glasses: solid state NMR and XPS structural studies of the glass system (Na2O)x(BPO4)1−x

Abstract: The structural organization of sodium borophosphate glasses with composition (Na(2)O)(x)(BPO(4))(1-x) (0.25 ≤x≤ 0.55) has been investigated by differential scanning calorimetry, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), as well as single- and double resonance (11)B and (31)P magic-angle spinning (MAS) NMR. (11)B MAS-NMR data indicate the dominance of anionic four-coordinated boron units, and (31)P MAS NMR reveals the successive transformation of neutral P(3) into singly charged P(2) units and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
88
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 31 publications
6
88
1
Order By: Relevance
“…11 The x = 0.8 and 1.0 samples show weak bands at 737 and 867 cm −1 evidencing the presence of Ge (2) and Ge (3) units, (GeO 2 ) stretch;sym and (GeO) stretch;sym , respectively. The weakness of these bands along with the observation of P…”
Section: −5mentioning
confidence: 99%
See 3 more Smart Citations
“…11 The x = 0.8 and 1.0 samples show weak bands at 737 and 867 cm −1 evidencing the presence of Ge (2) and Ge (3) units, (GeO 2 ) stretch;sym and (GeO) stretch;sym , respectively. The weakness of these bands along with the observation of P…”
Section: −5mentioning
confidence: 99%
“…and 1319 cm −1 that can be attributed to the (P−O−P) stretch;sym , (PO 2 ) stretch;(a)sym , and (PO) stretch;sym , respectively. 26 These bands reflect the expected presence of both P (2) and P ( . Older works suspect that Ge 6 or Ge 5 units cause a signal at around 670 cm −1 , 27 which has, however, been called into question in later works.…”
Section: −5mentioning
confidence: 99%
See 2 more Smart Citations
“…43 and did not find evidence for the formation of BPO 4 units in their glasses. For example, Rinke et al 44 showed that the Raman spectra of BPO 4 crystal has a strong peak at ∼490 cm −1 , weaker peaks at 1120 and 240 cm −1 , and finally minor peaks at 465 and 1080 cm −1 . In our Raman spectra presented and analyzed above, we do not see evidence of BPO 4 units as we do not see evidence of a peak at 240 cm −1…”
mentioning
confidence: 99%